2022
DOI: 10.3390/agronomy12102491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light, Temperature, Salinity, and Halopriming on Seed Germination and Seedling Growth of Hibiscus sabdariffa under Salinity Stress

Abstract: Salt stress is a serious and current global problem for crops. Due to climate change, the soil today has higher salinity levels than in past decades. Identifying temperature, light, and salinity that allow plants to germinate and grow is an ambitious challenge for the future. Hibiscus sabdariffa (H. sabdariffa) is a plant that undergoes abiotic stress during all stages of growth. The aim of this work was to identify the best conditions in terms of light, temperature, and salinity during the germination and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Considering the economic importance of this cultivar, we focused the next experiment on the physiological response of Borlotto, starting from sowing germinated seeds, either primed or not, in saline soil. Despite reports from the literature [62][63][64][65], priming was not sufficient to support plant growth in such conditions. This outcome had already been observed in our previous study on tomato plants [32], where an improvement in salt tolerance was observed when priming was followed by an acclimation phase to salinity.…”
Section: Effect Of Seed Priming On Bean Germination and Growthmentioning
confidence: 85%
“…Considering the economic importance of this cultivar, we focused the next experiment on the physiological response of Borlotto, starting from sowing germinated seeds, either primed or not, in saline soil. Despite reports from the literature [62][63][64][65], priming was not sufficient to support plant growth in such conditions. This outcome had already been observed in our previous study on tomato plants [32], where an improvement in salt tolerance was observed when priming was followed by an acclimation phase to salinity.…”
Section: Effect Of Seed Priming On Bean Germination and Growthmentioning
confidence: 85%
“…Additionally, it increased water use efficiency in field conditions compared to the control, which was significant in mitigating the adverse effects of water scarcity (El-Sanatawy et al, 2021). Halopriming has also been applied to Hibiscus sabdariffa seeds under salt stress conditions, leading to an increased germination rate and emergence percentage (Taghvaei et al, 2022).…”
Section: Haloprimingmentioning
confidence: 99%
“…The germination of seeds is one of the most critical stages of plants. Seeds tend to germinate when provided with favorable environmental conditions and factors necessary for germination such as; light, water, oxygen, and temperature (Taghvaei et al, 2022; Ankalaiah & Reddy, 2022a & 2022b; Rohini Latha, 2022). Nevertheless, some seeds fail to germinate even when the above favorable environmental conditions are provided, such seeds are said to be dormant (dormancy) (Guo et al, 2020;Luo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%